A first approach of beach sanding on the Black Sea Romanian’s coast - Beer, Albert (Technium EcoGeoMarine, 2023)
The Romanian coastline, which is subject to complex processes of geomorphological evolution due to beach sanding actions, as well as other natural and anthropogenic factors. Beach sanding is an important action in the maintenance and development of coastal areas, it provides protection against erosion, contributes to the formation and maintenance of beaches, as well as to the preservation of coastal ecosystems The main source of sand for Romanian beaches is coastal transport, i.e. the movement of sand along the coast under the action of values, current and wind. Naturally, there is some redistribution of sand along the coast, with an area where it accumulates and an area where it is lost. However, human intervention and other influences can disrupt this natural balance. In order to counteract the negative impact of insufficient sanding, various coastal management measures have been implemented in Romania. These include the artificial replenishment of beaches by bringing in additional sand from the seabed or other sources, as well as the construction of beach protection and stabilization works.